Prof. dr Vladan Virijević: Yugoslav-Turkish Economic Relations 1918-1941 (Kosovska Mitrovica: Faculty of Philosophy, 2018) - Deletić, Zdravko M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The article does not contain abstract.